Institutional permissiveness in the context of government-business relations - Sousa, André Luiz Castro de; Rocha, Robson Silva Soe; Abreu, Mônica Cavalcanti Sá de (Revista de Administração da UFSM, 2020)
Purpose - This article explores the extent to which business–government relations permeate socially irresponsible business activities. While existing theory provides traction in explaining the strength of the pressures to conform that emanate from the institutional environment, it does not adequately explain the conditions under which businesses might exercise discretion in choosing whether or not to conform to local standards of appropriateness and how local actors organize their responses accordingly. Methodology - The empirical evidence is based on an in-depth longitudinal case study developed in an industrial district of Fortaleza, Brazil. Data were collected from three sources, including semi-structured interviews. An inductive thematic analysis of narratives was conducted to investigate the interactions between the different institutional actors and their experiences of institutional change and renegotiation. Findings - It was found that the institutionalized forms of business–government relations are fundamentally permissive and personalized, being based on meeting specific and mutually opportunistic demands. We show that institutional permissiveness can make it possible for large firms to dominate an industrial area and force the government to reduce law enforcement. We demonstrate the historical evolution of forms of the appropriation of space and natural resources. Originality - Our theoretical contribution is to the concept of institutional permissiveness. Unlike other institutional streams, we argue that the concept of the institutional void is inadequate to the task of understanding business–government relations in emerging markets. We show how an institutional configuration can emerge that sustains the power relations and resource appropriations that reproduce social relations distinct from those found in the Anglo-American institutional environment, which does not configure institutional voids.